A study about effect of hydroxyurea on scholastic performance of children with sickle cell anemia - Nimisha Joshi,; Jain, Nilesh Jain; Jain, Pramila Ramawat (Indian Journal of Child Health, 2021)
Background: Sickle cell anemia (SCA) is the most common hemoglobinopathy affecting the population worldwide, is associated with high morbidity and mortality. Treatment with hydroxyurea (HU) has shown promising results by improving the clinical profile of patients. However, its effect on scholastic performance of children is yet to be explored. Objective: The objective of the study was to evaluate the effect of HU on scholastic performance in children affected with SCA. Methods: A prospective analytical study was conducted among 73 SCA patients between the ages of 5 and 14 years hospitalized or visiting the outpatient department at a tertiary care center on Central India. A fixed low dose of HU (20 mg/kg/day) was prescribed to individual patients at the start of the study. Patients were followed up for a period of 6 months at an interval of 2 months. Scholastic performance was evaluated based on school attendance and examination grades of child and was compared with results of previous year. Results: Only 54/73 patients successfully completed the study, among them 51.8% were male. Vaso-occlusive crisis (VOC) was the most common indication for initiating HU therapy. After 6 months of active therapy, significant improvement in scholastic performance was observed. Improvement in mean attendance from 63.98% to 68.09% was observed (p